Teste funcional sistemático estendido: uma contribuição na aplicação de critérios de teste caixa-preta - Vidal, Adriana Rocha (2011)
Building software involves a process composed of activities and methods. Even following these activities and using the proposed methods the resultant product may have some deviation with respect to its functional and nonfunctional requirements, not corresponding to the expected features. To minimize such problems, the test activity aims to ensure both the construction of the correct product and its correct construction. Since testing is considered a costly activity, research are conducted aiming at to make it feasible. This work ts in this context, in order improve the selection of test cases, thus increasing the quality of software products and the performance of testing guideline. It is interesting to note that, testing guideline is a fundamental artifact of the testing process and consists of test cases that, by de nition, execute a particular functionality of the program or check the suitability of the product over its speci ed requirements. Since the quality of the selected test cases have a great impact on the quality of the nal product, this work introduces the Extended Systematic Functional Test (ESFT) as a way to systematize the development and selection of test cases based on functional testing. A web system and a testing guideline used in certi cation were assessed using the ESFT in order to demonstrate the applicability and possible contributions of its use in terms of defect detection. The results are promising since the systematization, increases the number of selected test data, improves the detection of defects, and allow to justify why a particular test data is selected based on functional criteria.